Spectrum of Endocrine Disorders in Central Ghana - Osei Sarfo-Kantanka; Fred Stephen Sarfo; Eunice Oparebea Ansah; Ishmael Kyei (International Journal of Endocrinology)
Background. Although an increasing burden of endocrine disorders is recorded worldwide, the greatest increase is occurring in developing countries. However, the spectrum of these disorders is not well described in most developing countries. Objective. The objective of this study was to profile the frequency of endocrine disorders and their basic demographic characteristics in an endocrine outpatient clinic in Kumasi, central Ghana. Methods. A retrospective review was conducted on endocrine disorders seen over a five-year period between January 2011 and December 2015 at the outpatient endocrine clinic of Komfo Anokye Teaching Hospital. All medical records of patients seen at the endocrine clinic were reviewed by endocrinologists and all endocrinological diagnoses were classified according to ICD-10. Results. 3070 adults enrolled for care in the endocrine outpatient service between 2011 and 2015. This comprised 2056 females and 1014 males (female : male ratio of 2.0 : 1.0) with an overall median age of 54 (IQR, 41–64) years. The commonest primary endocrine disorders seen were diabetes, thyroid, and adrenal disorders at frequencies of 79.1%, 13.1%, and 2.2%, respectively. Conclusions. Type 2 diabetes and thyroid disorders represent by far the two commonest disorders seen at the endocrine clinic. The increased frequency and wide spectrum of endocrine disorders suggest the need for well-trained endocrinologists to improve the health of the population.